Biceps activity during windmill softball pitching - Rojas, I. L.; Provencher, M. T.; Bhatia, S.; Foucher, K. C.; Bach, B. R.; Romeo, A. A.; Wimmer, M. A.; Verma, N. N. (The American Journal of Sports Medicine, 2009)
Windmill pitching produces high forces and torques at the shoulder and elbow, making the biceps labrum complex susceptible to overuse injury. Little is known about the muscle firing patterns during a windmill pitch.